Quorum sensing in synthetic biology: A review. Issue 28 (December 2021) - Boo, Alice; Ledesma Amaro, Rodrigo; Stan, Guy-Bart
Abstract: In nature, quorum sensing is one of the mechanisms bacterial populations use to communicate with their own species or across species to coordinate behaviours. For the last 20 years, synthetic biologists have recognised the remarkable properties of quorum sensing to build genetic circuits responsive to population density. This has led to progress in designing dynamic, coordinated and sometimes multicellular systems for bioproduction in metabolic engineering and for increased spatial and temporal complexity in synthetic biology. In this review, we highlight recent works focused on using quorum sensing to engineer cell–cell behaviour. Highlights: Quorum sensing (QS) is increasingly used to coordinate behaviours in engineered bacterial populations. QS provides dynamical solutions to metabolic engineering and pattern formation. QS can be used to stabilise co-cultures for division of labour and microbiome engineering. Complex bio-based computations can be achieved by coordinating multiple strains with QS. Novel orthogonal QS systems are needed to engineer intra- and inter-kindgom communities.